Strategi Manajemen Unggul dalam Pengelolaan Sumber Daya Manusia untuk Meningkatkan Kinerja Pendidikan - Megaharti, Megaharti (ARZUSIN, 2024)
This study analyzes the implementation of Superior Management Strategies in Human Resource Management (HR) to improve educational performance in educational institutions. Through qualitative research methods with a case study approach, this research highlights strategic aspects such as planning, recruitment, training, and teacher performance management. The results show that the implementation of superior management strategies is effective in increasing efficiency, creating a positive work environment, and supporting the achievement of educational goals. The importance of collaboration between faculty, management staff, and external interested parties was also found to be key to the success of this strategy. This research provides practical guidance for educational institutions to integrate superior management strategies as an integral part of efforts to improve educational performance holistically.